2021
DOI: 10.1002/gj.4116
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimate variability during the last two millennia from the mudflats of Diu Island, Western India

Abstract: The climate variability over western India has been significantly influenced by the perturbations in the Indian summer monsoon (ISM) and thus, provides a crucial platform to investigate the paleomonsoon variations, weathering intensity, and sediment source. The mudflats of southern Saurashtra, western India are deprived of perennial rivers, but the region receives terrestrial contribution exclusively due to activation of seasonal rivers during the monsoon. In the present study, an attempt has been made to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 161 publications
0
19
0
Order By: Relevance
“…The rock/sediment geochemistry, U–Pb isotopes from accessory minerals (zircon, monazite, titanite, etc.) and mineral inclusions within zircon have been widely used to distinguish the rock/sediment source (Banerji et al, 2021a; Bruand, et al, 2016; Basu, Bickford, & Deasy, 2016; Joshi, Goswami, Banerji, & Shankar, 2021a; Slabunov et al, 2017). Studies have demonstrated that the chemical composition of fine‐grained sediments is related to that of their source regions (Dey, Rai, & Chaki, 2009; Manikyamba, Kerrich, González‐Álvarez, Mathur, & Khanna, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rock/sediment geochemistry, U–Pb isotopes from accessory minerals (zircon, monazite, titanite, etc.) and mineral inclusions within zircon have been widely used to distinguish the rock/sediment source (Banerji et al, 2021a; Bruand, et al, 2016; Basu, Bickford, & Deasy, 2016; Joshi, Goswami, Banerji, & Shankar, 2021a; Slabunov et al, 2017). Studies have demonstrated that the chemical composition of fine‐grained sediments is related to that of their source regions (Dey, Rai, & Chaki, 2009; Manikyamba, Kerrich, González‐Álvarez, Mathur, & Khanna, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Mixing and homogenization of compositionally diverse source rocks due to the combined processes of erosion, transportation, deposition, and diagenesis render Post‐Archean sedimentary rocks with a certain degree of geochemical uniformity (McLennan & Taylor, 1991; Taylor, Rudnick, McLennan, & Eriksson, 1986). However, previous studies (Absar, Raza, Roy, Naqvi, & Roy, 2009; Banerji, Bhushan, Joshi, Shaji, & Jull, 2021a; Basu, Dandele, Kumar, Achar, & Umamaheswar, 2017; Bhat & Ghosh, 2001; El‐Bialy, 2013; McLennan, Hemming, Taylor, & Eriksson, 1995; Shukla, George, & Ray, 2020) have suggested that the geochemical characters of sediments and sedimentary rocks can yield reliable insights into the provenance, prevalent weathering conditions, secondary processes (K‐metasomatism), and tectonic setting of the depositional basin.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Several studies of lacustrine sediments from China suggest that chemical weathering proxies are ideal tools to reconstruct the monsoonal strength in the region (Huang, Wei, & Li, 2018; Liu et al, 2014; Wang et al, 2019; Zhang, Ming, & Shi, 2016). The geochemical proxies from lacustrine sediments of the northern (Babeesh, Achyuthan, & Resmi, 2019; Bhushan, Sati, & Rana, 2018; Shah, Achyuthan, & Lone, 2020) and northwestern India (Banerji, Bhushan, Joshi, Shaji, & Jull, 2021; Roy, Smykatz‐Kloss, & Morton, 2008; Sinha, Smykatz‐Kloss, & Stüben, 2006) were employed to infer the past changes in rainfall. However, only a few studies have been done on the geochemical properties of lake sediments from southern India.…”
Section: Introductionmentioning
confidence: 99%
“…The geochemical proxies from lacustrine sediments of the northern (Babeesh, Achyuthan, & Resmi, 2019;Bhushan, Sati, & Rana, 2018;Shah, Achyuthan, & Lone, 2020) and northwestern India (Banerji, Bhushan, Joshi, Shaji, & Jull, 2021;Roy, Smykatz-Kloss, & Morton, 2008;Sinha, Smykatz-Kloss, & Stüben, 2006) were employed to infer the past changes in rainfall. However, only a few studies have been done on the geochemical properties of lake sediments from southern India.…”
mentioning
confidence: 99%